1998
DOI: 10.1089/acm.1998.4.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Herbal Remedies: The Case of an Outbreak of Terminal Renal Failure in Belgium (Chinese Herbs Nephropathy)

Abstract: At least 100 cases of extensive interstitial fibrosis of the kidneys were observed in Belgium in women who had followed a weight-loss regimen that included the use of Chinese herbs. The possible relation between the renal disease and these Chinese herbs was investigated. It was shown that the prescribed Chinese herb called Stephania tetrandra was, in fact, inadvertently replaced by another Chinese herb, namely Aristolochia fangchi in the powdered extracts delivered in Belgium and in France. The development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(129 citation statements)
references
References 17 publications
2
125
0
2
Order By: Relevance
“…accord with findings in human populations, where only a small fraction of AA-exposed individuals develop renal toxicity and/or urothelial cancer (4,23,24). The genetic basis for such relative susceptibility is yet to be determined.…”
Section: Discussionsupporting
confidence: 75%
“…accord with findings in human populations, where only a small fraction of AA-exposed individuals develop renal toxicity and/or urothelial cancer (4,23,24). The genetic basis for such relative susceptibility is yet to be determined.…”
Section: Discussionsupporting
confidence: 75%
“…Vanherweghem (1998) described the occurrence of at least 100 cases of extensive interstitial fibrosis of the kidneys observed in Belgian women who had followed a weight loss program which included the use of Chinese herbs. Investigations following these cases suggested that (Han Fang Ji " ") was in fact mistakenly replaced with another Chinese herb Aristolochia fangchi (Guang Fang Ji " "), as evident from the absence of tetrandrine, a characteristic alkaloid in Stephania tetrandra, in the capsules taken by patients.…”
Section: Less-than-lifetime Exposurementioning
confidence: 99%
“…Investigations following these cases suggested that (Han Fang Ji " ") was in fact mistakenly replaced with another Chinese herb Aristolochia fangchi (Guang Fang Ji " "), as evident from the absence of tetrandrine, a characteristic alkaloid in Stephania tetrandra, in the capsules taken by patients. In addition, it was noted that the Chinese characters and pinyin name of the 2 herbs were similar with the exception of the prefix, and hence could have been easily confused for each other (Vanherweghem 1998). …”
Section: Less-than-lifetime Exposurementioning
confidence: 99%
“…EN does not occur in children, but the inhabitants that have left the endemic area after over a decade of residence there are also known to develop EN. Patients with AAN usually developed the disease after several years of treatment with Chinese herbs (10,11). In some cases nephropathy was characterised by a rapid deterioration in renal function, with initial serum creatinine doubling within about three months.…”
Section: Epidemiological Features Of Endemic Nephropathy and Chinese mentioning
confidence: 99%